Determination of 5-aminolevulinic acid in liquid cultures of purple non-sulfur photosynthesizing bacteria by high performance liquid chromatography - E. V. Minasyan; A. H. Tsaturyan; N. K. Kalantaryan; B. A. Harutyunyan (ՀՀ ԳԱԱ հրատ.)
A method of high-performance liquid chromatography (HPLC) was used for determination of producers of 5-aminolevulinic acid (ALA) in liquid cultures of purple non-sulfur photosynthesizing bacteria. ALA is derivatized with formaldehyde in which acetyl acetone in the presence of the amine group of ALA forms the fluorescent product 3,5-diacetyl-1,4-dihydro lutidine. Բարձր արդյունավետության հեղուկային քրոմատոգրաֆիայի (ԲԱՀՔ) մեթոդով նույնականացվել են ծիրանագույն ոչ ծծմբային ֆոտոսինթեզող բակտերիաների կուլտուրալ հեղուկներում 5-ամինալևուլինաթթուն: Մեթոդը իրականացվել է < Waters Separations module 2695 > (ԱՄՆ) հեղուկային քրոմատոգրաֆի վրա՝ ֆլյուրոսցենտային դետեկցմամբ: Методом высокоэффективной жидкостной хроматографии определено содержание 5-аминолевулиновой кислоты (АЛК) в культуральных жидкостях фотосинтезирующих несерных пурпурных бактерий. Разработка метода осуществлялась на жидкостном хроматографе “Waters Separations module 2695” (США) с помощью флуоресцентного детектирования.
Keywords: Analytic Chemistry